Innovative Learning through Fun Thinkers Media Based on Fill the Blank Question - Buana Rosnata, Ni Putu Feby Mulia; Agustiana, I Gusti Ayu Tri; Dibia, I Ketut (Universitas Pendidikan Ganesha, 2021)
Lack of student understanding of the material provided online by the teacher, students feel bored with monotonous learning using mobile phones, teachers provide materials and assignments through student books, the media used is still simple and less attractive. This study aims to develop media fun thinkers based on fill the blank questions for grade 1 elementary school students on theme 3 of my activities. Media development in this study is guided by the ADDIE model procedure which consists of several stages, namely analysis (Analyze), planning (Design), development (Development), implementation (Implementation), and evaluation (Evaluation). The trial subjects of this study consisted of 2 subject matter experts, 2 media experts, 2 practitioner responses, and 10 student responses (small groups). The data collected in this study, namely qualitative data and quantitative data. Data was collected using a questionnaire method with the distribution of rating scale instruments. The results showed that the average validity and reliability scores from the point of view of material experts were 4.3 with very valid qualifications and 93% with reliable qualifications, in terms of media experts it was 4.4 with very valid qualifications and 92% with reliable qualifications, from In terms of practitioner responses, it is 4.6 with very valid qualifications and 96% with reliable qualifications, and in terms of student responses it is 4.8 with very valid qualifications and 97% with reliable qualifications. This shows that the media fun thinkers based on fill the blank questions for elementary school students in grade 1 on theme 3 of my activities is declared suitable for use in learning. The implications of this research are expected to help students during online learning.